Efficient intracellular delivery of native proteins facilitated by preorganized guanidiniums on pillar[5]arene skeleton. (April 2022) - Guo, Shuwen; Huang, Qiaoxian; Wei, Jianwen; Wang, Shengpeng; Wang, Yitao; Wang, Leyong; Wang, Ruibing
Highlights: Guanidinium-pillar[5] arene (GP5) may bind proteins to form nanocomplexes. GP5 facilitates binding of proteins and cellular surface. GP5 efficiently delivers proteins of different isoelectric points intracellularly. The bioactivity of intracellularly delivered proteins are well maintained. Graphical Abstract: Guanidinium perfunctionalized pillar[5]arene (GP5) showed excellent potency of binding and delivering proteins of different isoelectric points and sizes into cells, and the bioactivities of the proteins were well maintained after intracellular delivery. The densely pre-organized guanidinium groups on the pillar[5]arene skeleton not only facilitate GP5 to bind proteins via multiple salt bridges, but also promote cellular uptake of GP5 @protein complexes. ga1 Abstract: Due to membrane impermeability of proteins, intracellular delivery of protein is of significant challenge. Although numerous protein carriers have been reported, it remains difficult to efficiently deliver proteins with different isoelectric points into cells. Herein, guanidinium perfunctionalized pillar[5]arene (GP5) was employed for efficient delivery of proteins with different isoelectric points into different cell lines, and the bioactivities of the proteins were well maintained after intracellular delivery. After comparison with linear cell-penetrating peptides, unsymmetrical guanidinium-macrocycles, primary and quaternary ammonium functionalized pillar[5]arene derivatives, and the monomer of GP5, the high protein delivery potency of GP5 was mainly attributed to the densely pre-organized guanidinium groups on both sides of the pillar[5]arene skeleton, which could not only facilitate GP5 to bind with proteins to form protein nano-aggregates, but also promote cellular uptake of proteins via interactions with cellular surface. This study offers important new insights to the design and development of cell-penetrating peptide mimetic molecules for protein transductions.